PRIORITY DIRECTIONS AND PERSPECTIVES OF ENSURING THE TRANSPARENCY OF STATE POLICY ON YOUTH IN UZBEKISTAN - Khudoberdiyev Jamoliddin (Galaxy International Interdisciplinary Research Journal, 2024)
As a result of the reforms carried out in our country, today, efforts are being made to ensure the transparency and openness of all areas and directions of state activity.